Nuprl Definition : coW-game2

coW-game2(a.B[a];w;w'';w') ==
  <copath(a.B[a];w) × copath(a.B[a];w'') × copath(a.B[a];w')
  , <(), (), ()>
  , λx,y. let u,z,v in 
         let u',z',v' in 
         ((copath-length(u') (copath-length(u) 1) ∈ ℤ)
         ∧ copathAgree(a.B[a];w;u;u')
         ∧ (v v' ∈ copath(a.B[a];w'))
         ∧ (z z' ∈ copath(a.B[a];w'')))
         ∨ (((u u' ∈ copath(a.B[a];w)) ∧ (z z' ∈ copath(a.B[a];w'')))
           ∧ (copath-length(v') (copath-length(v) 1) ∈ ℤ)
           ∧ copathAgree(a.B[a];w';v;v'))
  , λx,y. let u,z,v in 
         let u',z',v' in 
         ((copath-length(z') (copath-length(z) 1) ∈ ℤ)
         ∧ copathAgree(a.B[a];w'';z;z')
         ∧ (((copath-length(u') (copath-length(u) 1) ∈ ℤ)
           ∧ copathAgree(a.B[a];w;u;u')
           ∧ (v v' ∈ copath(a.B[a];w')))
           ∨ ((u u' ∈ copath(a.B[a];w))
             ∧ (copath-length(v') (copath-length(v) 1) ∈ ℤ)
             ∧ copathAgree(a.B[a];w';v;v'))))
         ∧ (copath-length(u') copath-length(v') ∈ ℤ)
         ∧ (copath-length(z') copath-length(v') ∈ ℤ)>



Definitions occuring in Statement :  copathAgree: copathAgree(a.B[a];w;x;y) copath-nil: () copath-length: copath-length(p) copath: copath(a.B[a];w) spreadn: spread3 or: P ∨ Q and: P ∧ Q lambda: λx.A[x] pair: <a, b> product: x:A × B[x] add: m natural_number: $n int: equal: t ∈ T
Definitions occuring in definition :  copath-length: copath-length(p) int: equal: t ∈ T and: P ∧ Q copathAgree: copathAgree(a.B[a];w;x;y) natural_number: $n add: m copath: copath(a.B[a];w) or: P ∨ Q spreadn: spread3 lambda: λx.A[x] pair: <a, b> copath-nil: () product: x:A × B[x]
FDL editor aliases :  coW-game2

Latex:
coW-game2(a.B[a];w;w'';w')  ==
    <copath(a.B[a];w)  \mtimes{}  copath(a.B[a];w'')  \mtimes{}  copath(a.B[a];w')
    ,  <(),  (),  ()>
    ,  \mlambda{}x,y.  let  u,z,v  =  x  in 
                  let  u',z',v'  =  y  in 
                  ((copath-length(u')  =  (copath-length(u)  +  1))
                  \mwedge{}  copathAgree(a.B[a];w;u;u')
                  \mwedge{}  (v  =  v')
                  \mwedge{}  (z  =  z'))
                  \mvee{}  (((u  =  u')  \mwedge{}  (z  =  z'))
                      \mwedge{}  (copath-length(v')  =  (copath-length(v)  +  1))
                      \mwedge{}  copathAgree(a.B[a];w';v;v'))
    ,  \mlambda{}x,y.  let  u,z,v  =  x  in 
                  let  u',z',v'  =  y  in 
                  ((copath-length(z')  =  (copath-length(z)  +  1))
                  \mwedge{}  copathAgree(a.B[a];w'';z;z')
                  \mwedge{}  (((copath-length(u')  =  (copath-length(u)  +  1))  \mwedge{}  copathAgree(a.B[a];w;u;u')  \mwedge{}  (v  =  v'))
                      \mvee{}  ((u  =  u')
                          \mwedge{}  (copath-length(v')  =  (copath-length(v)  +  1))
                          \mwedge{}  copathAgree(a.B[a];w';v;v'))))
                  \mwedge{}  (copath-length(u')  =  copath-length(v'))
                  \mwedge{}  (copath-length(z')  =  copath-length(v'))>



Date html generated: 2018_07_25-PM-01_43_16
Last ObjectModification: 2018_06_22-PM-05_14_16

Theory : co-recursion


Home Index